English Language Teacher Education: Rewriting S-1 National Curriculum - M. Soenardi Djiwandono (TEFLIN Journal: A publication on the teaching and learning of English, 1999)
As part of an overall attempt to improve secondary school teacher education, a program has been launched to review and develop the national curriculum (KURNAS) of English language teacher education in Indonesia as a means to improve the quality of teachers of English. The new curriculum is at the same time intended to be a revision of the 1995 national curriculum supposedly in use now. For the purpose a team of three members was appointed by the Secondary School Teacher Development Project (nationally known as Proyek PGSM), comprising English teaching professionalls from Universitas Negeri Malang, GAJAHMADA UNIVERSITY, and a senior high school teacher of English. Following a study of the existing documents related to ELT in Indonesia, an initial draft was written and gradually developed following a series of discussions and exchanges of ideas with teachers and profesionalls in the field of ELT. By the 3 rd year of the appointment of the team, the draft for the new KURNAS comprising Books I, II, and III, has been completed and ready for a try-out. The try-out was intended to put into practise the Intensive Course (IC) Program as one of the most important components of the new KURNAS for the development of fluency in English as an essential basis for the preparation of competent high school teachers of English. This article describes the background and the underlying principles of the curriculum revision, along with the classification and identification of courses, descriptions of courses their and syllabus outlines.